2000
DOI: 10.1037/0882-7974.15.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Psychological treatment of secondary insomnia.

Abstract: Psychological treatment of insomnia has focused on primary insomnia (i.e., having a psychological origin). Secondary insomnia, sleep disturbance caused by a psychiatric or medical disorder, although it is more common than primary insomnia, has received very little attention as a result of the belief that it would be refractory to treatment. The present study randomly assigned older adults with secondary insomnia to a treatment group, 4 sessions composed of relaxation and stimulus control, or a no-treatment con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
1
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(144 citation statements)
references
References 37 publications
8
128
1
5
Order By: Relevance
“…Several studies have documented the benefits of insomnia-specific treatment in older adults with either comorbid medical or psychological conditions (Lichstein, Wilson, & Johnson, 2000;Pallesen et al, 2003;Rybarczyk, Lopez, Benson, Alsten, & Stepanski, 2002;Rybarczyk et al, 2005). One study found that older adults with chronic obstructive pulmonary disease, osteoarthritis or coronary artery disease benefited from group CBT and, in addition to improving sleep continuity, treatment of insomnia was associated with enhanced sleep satisfaction and quality of life (Rybarczyk et al, 2005).…”
Section: Insomnia In Older Adultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have documented the benefits of insomnia-specific treatment in older adults with either comorbid medical or psychological conditions (Lichstein, Wilson, & Johnson, 2000;Pallesen et al, 2003;Rybarczyk, Lopez, Benson, Alsten, & Stepanski, 2002;Rybarczyk et al, 2005). One study found that older adults with chronic obstructive pulmonary disease, osteoarthritis or coronary artery disease benefited from group CBT and, in addition to improving sleep continuity, treatment of insomnia was associated with enhanced sleep satisfaction and quality of life (Rybarczyk et al, 2005).…”
Section: Insomnia In Older Adultsmentioning
confidence: 99%
“…Several controlled studies have shown that CBT is effective for insomnia associated with chronic pain (Currie, Wilson, Pontefract, & deLaplante, 2000), fibromyalgia (Edinger, Wohlgemuth, Krystal, & Rice, 2005), cancer (Espie et al, 2008;Savard, Simard, Ivers, & Morin, 2005), and with various medical conditions in older adults (Lichstein, Wilson, & Johnson, 2000;Rybarczyk et al, 2005).…”
Section: Insomnia 12 Treatment Of Comorbid Insomniamentioning
confidence: 99%
See 1 more Smart Citation
“…36 Also, studies reporting a RFNE in insomniacs have largely excluded patients with significant psychiatric illnesses such as depression; however, it has been shown that insomnia and depression are frequently comorbid conditions, with over 90% of depressed patients suffering from sleep complaints. 21,22 Some studies on first night adaptation effects in depressed patients have observed a reduced or absent FNE 2,9,23 ; however, it is unknown whether patients suffering from both insomnia and depression exhibit similar laboratory adaptation effects as those suffering from only one of these disorders.…”
Section: Psgmentioning
confidence: 99%
“…We found six between-group design studies and one multiple baseline study that supported multicomponent CBT as an EBT (Hoelscher & Edinger, 1988;Lichstein, Wilson, & Johnson, 2000;McCurry, Logsdon, Vitiello, & Teri, 1998;Morin, Colecchi, Stone, Sood, & Brink, 1999;Morin, Kowatch, Barry, & Walton, 1993;Rybarczyk, Lopez, Benson, Alsten, & Stepanski, 2002;. Table 2 contains basic details of these studies.…”
Section: Multicomponent Cbtmentioning
confidence: 99%